THE IMPACT OF ACTIVE OR PAST MATERNAL ANOREXIA NERVOSA ON FETAL GROWTH AND DEVELOPMENT - Julia Procyk; Marta Danuta Cendrowska; Aleksandra Klukowska; Beata Choromańska; Karolina Stępień; Justyna Berent; Paulina Rzepa; Barbara Ponitka; Julia Maszewska; Szymon Milnerowicz; Łukasz Brzost; Wiktoria Szumlińska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Anorexia nervosa (AN) is a psychiatric eating disorder that disrupts the hypothalamic–pituitary–ovarian axis, often causing amenorrhea and delaying conception. Although remission can restore fertility, both active and past AN are linked to obstetric and neonatal complications. Aim of the Study: We aimed to systematically review the current knowledge about the effect of maternal anorexia nervosa on fetal growth and development. Methodology: PubMed was searched (2005–2025) for original English clinical studies on maternal AN and fetal outcomes; reviews, case reports, and non‐clinical articles were excluded, resulting in 17 eligible full‐text studies. Results: The most consistently reported finding was a significantly lower birth weight in infants born to mothers with a history of past or active AN. The main cause of low birth weight was low maternal pre-pregnancy body mass index (BMI) and insufficient weight gain during pregnancy. Other common adverse neonatal outcomes included small-for-gestational-age, preterm birth, and reduced head circumference, the latter being associated with potential neurocognitive developmental delays. The risk of complications was markedly higher for women with active AN during pregnancy. Conclusions: Maternal AN increases the risk of adverse obstetric and neonatal outcomes. Multidisciplinary care with careful monitoring of maternal weight, nutritional status, and mental health is essential to minimize risks and optimize perinatal outcomes.